Legal Responsibility of Insurance Companies for Actions of Default in Insurance Agreements - Muhammad - Yasid; Gomgom TP Siregar; Muhammad Ansori Lubis; Ria Sintha Devi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Insurance is one way to help the community in diverting risks from events that are not necessarily going to happen. In this case the insurance company as the insurer has an obligation to fulfill the agreement that has been agreed by him with the insured which is called the policy agreement. However, in practice, not a few insurance companies default on insurance agreements. This study uses a normative juridical method with a qualitative descriptive analysis. Based on the results of the study it was concluded that the legal responsibility that must be carried out by the insurance company against default in the insurance agreement is the fulfillment of the rights of the policyholder as the insured of the insurance, namely compensation to the insured for achievements that were not carried out by the insurance company. The insured party can sue the insurance company if it defaults, besides that if the insurance company defaults, the insurance company can be given sanctions such as written warnings, fines, restrictions on business activities, up to revocation of business licenses